Comparison of a Personalized Prostate Biopsy Pattern With Traditional Transrectal Prostate Biopsy: Different Cancer Detection Rate - Jiang, Xin; Qu, Sifeng; Zhu, Yaofeng; Wang, Shuo; Sun, Haoyu; Guo, Hu; Shi, Benkang; Chen, Shouzhen (Frontiers in Cell and Developmental Biology, 2022)
Background: In terms of prostate biopsy approaches, it is difficult to reach the ventral central region of the prostate with the traditional transrectal prostate biopsy, while with the transperineal biopsy, the tumor in the dorsolateral region of the prostate is easily missed. However, until now, no studies have investigated the biopsy accuracy in the selective application of transrectal or transperineal biopsies according to the lesion site. Methods: We developed a personalized prostate biopsy pattern and the biopsy approach was selected individually according to the lesion site. We compared it with the traditional transrectal prostate biopsy method to evaluate the efficiency. Patients (n = 351) who underwent prostate biopsy at Qilu Hospital of Shandong University from January 2018 to October 2020 were divided into two groups, including the traditional transrectal prostate biopsy group (n = 236) and the personalized group (n = 115). The data from patients, including clinical characteristics, biopsy results, and complications, were analyzed. Results: The clinical characteristics of the two groups were similar. The total detection rate of prostate cancer in the personalized group was 49.6%, which was significantly higher than 38.1% in the traditional group (p = 0.023). When prostate-specific antigen was <20 ng/ml, the detection rates of the two groups were 30.4 and 19.3%, respectively (p = 0.039). The PI-RADS was positively associated with high-grade prostate cancer in the personalized group. Patients with complications in the traditional transrectal systematic method group accounted for 6.8%, and those in the personalized group complications through the transrectal and transperineal approaches accounted for 7.1 and 4.1%, respectively. The most common complications in the transrectal group were fever and rectal bleeding, and those in the transperineal group were hematuria and urinary retention. Conclusion: Compared with traditional transrectal prostate biopsy, the personalized biopsy pattern improved the detection rate of prostate cancer. The complications of the transrectal approach were much higher than those in the transperineal approach.